Comparison of desiccant air conditioning systems with different indirect evaporative air coolers. (1st June 2016) - Pandelidis, Demis; Anisimov, Sergey; Worek, William M.; Drąg, Paweł
Highlights: A numerical study of desiccant air conditioning systems is presented. The ε -NTU model is used for the analysis. Different arrangements of the desiccant systems were compared. The systems were compared under different operating conditions. Abstract: This paper presents a numerical analysis of three desiccant air-conditioning systems equipped with different indirect evaporative air coolers: (1) the cross-flow Maisotsenko cycle heat and mass exchanger (HMX), (2) the regenerative counter-flow Maisotsenko cycle heat and mass exchanger and (3) the standard cross-flow evaporative air cooler. To analyze the desiccant wheel and the indirect evaporative air coolers, the modified ε -NTU-model was used. The simulations were performed under assumption that the desiccant wheel is regenerated with air heated to relatively low temperature values (50–60 °C), which can be produced with solar panels in typical moderate climatic conditions. It was established that the main advantage of the presented solutions is that they can provide comfort conditions even with less effective dehumidification. The different systems were compared under variable selected operational factors (i.e. inlet air temperature, humidity and regeneration air temperature). The analysis allowed establishing the advantages and disadvantages of presented solutions and allowed estimating their application potential.